Carbon source–sink limitations differ between two species with contrasting growth strategies. (22nd September 2016) - Burnett, Angela C.; Rogers, Alistair; Rees, Mark; Osborne, Colin P.
Abstract: Understanding how carbon source and sink strengths limit plant growth is a critical knowledge gap that hinders efforts to maximize crop yield. We investigated how differences in growth rate arise from source–sink limitations, using a model system comparing a fast‐growing domesticated annual barley ( Hordeum vulgare cv. NFC Tipple) with a slow‐growing wild perennial relative ( Hordeum bulbosum ). Source strength was manipulated by growing plants at sub‐ambient and elevated CO2 concentrations ([CO2 ]). Limitations on vegetative growth imposed by source and sink were diagnosed by measuring relative growth rate, developmental plasticity, photosynthesis and major carbon and nitrogen metabolite pools. Growth was sink limited in the annual but source limited in the perennial. RGR and carbon acquisition were higher in the annual, but photosynthesis responded weakly to elevated [CO2 ] indicating that source strength was near maximal at current [CO2 ]. In contrast, photosynthetic rate and sink development responded strongly to elevated [CO2 ] in the perennial, indicating significant source limitation. Sink limitation was avoided in the perennial by high sink plasticity: a marked increase in tillering and root:shoot ratio at elevated [CO2 ], and lower non‐structural carbohydrate accumulation. Alleviating sink limitation during vegetative development could be important for maximizing growth of elite cereals under future elevated [CO2 ]. Abstract : Understanding the limitation of plant growth by carbon source or sink capacity is critical for maximizing crop yield. Growth in a fast‐growing domesticated annual barley species is carbon sink limited during vegetative development, whilst growth in a slow‐growing wild perennial barley species is carbon source limited. Alleviating sink limitation during vegetative development could be important for maximizing the growth potential of elite cereal crops under future elevated CO2 .